Handbook on Advances in Remote Sensing and Geographic Information Systems Paradigms and Applications in Forest Landscape Modeling - Favorskaya, Margarita N.; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the latest advances in remote-sensing and geographic information systems and applications. It is divided into four parts, focusing on Airborne Light Detection and Ranging (LiDAR) and Optical Measurements of Forests; Individual Tree Modelling; Landscape Scene Modelling; and Forest Eco-system Modelling. Given the scope of its coverage, the book offers a valuable resource for students, researchers, practitioners, and educators interested in remote sensing and geographic information systems and applications.
Innovations in Remote Sensing of Forests -- Overview of LiDAR Technologies and Equipment for Land Cover Scanning -- Software Tools for Terrain and Forest Modelling -- Data Fusion for Evaluation of Woodland Parameters -- Tree Modelling in Virtual Reality Environment -- Realistic Tree Modelling -- Digital Modelling of Terrain Surface -- Texturing of Landscape Scenes -- Large Scene Rendering -- Scene Rendering under Meteorological Impacts -- Lighting and Shadows Rendering in Natural Scenes -- Modelling of Forest Ecosystems.
Keywords: Computational intelligence; Geographic information systems; Signal processing; Artificial intelligence; Computational Intelligence; Geographical Information System; Signal, Speech and Image Processing; Artificial Intelligence